Daily Optional Physical Education Does Not Counteract Increasing Inactivity by Age among Adolescents - Zsuzsa Lábiscsák-Erdélyi; Annamária Somhegyi; Ilona Veres-Balajti; Karolina Kósa (MDPI AG, 2023)
Background: This paper describes the outcomes of an integrated health promotion programme implemented in a Hungarian high school offering health education in the curriculum, daily optional physical education, teacher training in applying a person-centered approach in teaching, and parental involvement in school activities. Methods: The evaluation used mixed methods of which results of the before-6-months-after quantitative survey among pupils is described. The health status and behaviour of students were assessed by applying the Hungarian version of the HBSC questionnaire. Results: Significant improvement was found in the self-rated health of girls (6.6% increase in being of excellent health, p = 0.04), and the consumption of sweets and sugary soft drinks decreased significantly for both genders (boys: −10.2%, p = 0.01; girls: −6.06%, p = 0.04). However, the proportion of physically inactive girls significantly increased (girls: 11.2%, p = 0.01), and substance use did not change significantly. Discussion and conclusions: The intervention had significant positive impacts on subjective health and dietary habits and could counteract the secular trend of increasing tobacco, alcohol, and drug consumption by age among adolescents, but this unfortunately does not include physical inactivity. Offsetting the most widespread health risk behavior, physical inactivity, may require mandatory daily physical education in schools.